Physicochemical and Sensory Properties of Cookies Produced from Peanut (Arachis hypogaea L.) Skin (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Cookies are a popular snack enjoyed worldwide but missing some nutritional components. As a byproduct of processing peanuts, peanut skin is high in procyanidin, fiber, and catechins. As far as we know, no cookies are composed of peanut skin. Thus, this study aims to determine the physicochemical characteristics and their sensory acceptability of various formulations of peanut skin cookies. Four cookie formulations with peanut skin powder (PSP) percentages of 0, 10, 20, and 30% were examined for color and hardness. When compared to control cookies, the proximate analysis showed 30% of PSP cookies was significantly higher than all formulations in all analyses except for carbohydrates, whereby the result for the highest concentration of peanut skin in cookies is 3.11% moisture, 1.48% ash, 25.92% fat, 3.33% fibre, 6.56% protein, and 56.60% carbohydrate. The hardness and fracturability of peanut skin cookies were higher than control cookies while colour analysis showed that the addition of PSP caused the cookies to become darker. Sensory evaluation indicated that 10% of PSP in cookies was the most acceptable to the panellist, while 30% of PSP in cookies received the lowest acceptance due to the bitter taste and hard texture of cookies. In conclusion, incorporating PSP into cookies affects the nutritional value of the cookies in fibre content but with limited acceptability among consumers.
Keywords: Peanut skin; Cookie; Proximate analysis; Sensory analysis; Peanut skin powder